Single-nucleotide polymorphisms in genes associated with the vitamin D pathway related to clinical and therapeutic outcomes of American tegumentary leishmaniasis - Oliveira, Iara Barreto Neves; Nunes, Ramon Vieira; Leite, Vanessa Rafaela Milhomem Cruz; Araújo, Camila Freire; Silveira, Murilo Barros; Pinto, Sebastião Alves; Lamounier, Lorena Andrade; Borges, Clayton Luiz; Martins, Edésio; Porto, Iane de Oliveira Pires; Gomes, Rodrigo Saar; Ribeiro-Dias, Fátima (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe vitamin D pathway contributes to the microbicidal activity of macrophages against Leishmania infection. In addition to induction of this pathway, interferon-gamma (IFNγ), interleukin (IL)-15, and IL32γ are part of a network of pro-inflammatory cytokines. The aim of this study was to evaluate single-nucleotide polymorphisms (SNPs) in the components of the vitamin D pathway and associated cytokine genes that could be related to resistance or susceptibility to American tegumentary leishmaniasis (ATL).MethodsThe expressions of IFNG, IL15, IL32, CYP27B1, VDR, and other pro-inflammatory cytokines TNF, IL6, and IL17 genes were evaluated using real-time polymerase chain reaction (qPCR) in lesions of patients with localized cutaneous leishmaniasis (LCL) or mucosal leishmaniasis (ML). SNP genotypes/alleles (in IL15, IL32, CYP27B1, and VDR) were evaluated by TaqMan PCR assays using DNA from the blood of patients and healthy individuals. Serum vitamin D levels were determined by chemiluminescence.ResultsVitamin D pathway-associated genes were expressed in cutaneous as well as mucosal lesions. IFNG, IL6, and IL17 were more highly expressed in ML than in LCL. In contrast, IL32γ/CYP27B1/VDR mRNAs were mainly correlated in LCL, and IL32γ in ML makes strong connections with all cytokines. The SNP IL32 rs1555001 was less frequent in patients with ML. In addition, some SNPs appear to influence the VDR and CYP27B1 (IL15 rs10519613 and IL15 rs3775597) and IL6 (VDR rs7975232) expressions in LCL and the IL17 expression in ML (IL15 rs3775597). Gene expression was also correlated with clinical parameters, such as number of lesions (CYP27B1 mRNA) and treatment failure (VDR mRNA). In addition, one SNP was associated with treatment failure in ML (VDR rs7975232).ConclusionsOur findings suggested that some SNPs in the vitamin D pathway-associated genes can be related to resistance and therapeutic outcomes of ATL. They are promising candidates that need to be further evaluated to understand their biological effects in the control or immunopathogenesis of ATL.